2017
DOI: 10.1016/j.biopsycho.2017.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Fear acquisition and liking of out-group and in-group members: Learning bias or attention?

Abstract: The present study explores the notion of an out-group fear learning bias that is characterized by facilitated fear acquisition toward harm-doing out-group members. Participants were conditioned with two in-group and two out-group faces as conditioned stimuli. During acquisition, one in-group and one out-group face was paired with an aversive shock whereas the other in-group and out-group face was presented without shock. Psychophysiological measures of fear conditioning (skin conductance and pupil size) and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Preparedness theory's application in associative learning experiments with social stimuli (e.g., Navarrete et al, ) is not without critics. Mallan, Lipp, and Cochrane () argue that fear learning toward outgroups does not meet the necessary conditions to satisfy the strict criteria of preparedness (see also Koenig et al, ; Maia, ). Prepared associations are easily acquired, resistant to extinction, and are cognitively irrational in comparison to unprepared associations (Öhman & Mineka, ).…”
Section: The Learning Paradigm and Its Application To Social Stimulimentioning
confidence: 99%
“…Preparedness theory's application in associative learning experiments with social stimuli (e.g., Navarrete et al, ) is not without critics. Mallan, Lipp, and Cochrane () argue that fear learning toward outgroups does not meet the necessary conditions to satisfy the strict criteria of preparedness (see also Koenig et al, ; Maia, ). Prepared associations are easily acquired, resistant to extinction, and are cognitively irrational in comparison to unprepared associations (Öhman & Mineka, ).…”
Section: The Learning Paradigm and Its Application To Social Stimulimentioning
confidence: 99%
“…Importantly, instead of taking an average (or peak) pupil size over the entire trial period, or within pre-defined time bins (García-Palacios et al, 2018;Jentsch et al, 2020;Koenig et al, 2017;Leuchs et al, 2017), the differential pupil CRs we observed held true for time windows that were derived from the data themselves.…”
Section: Pupil Datamentioning
confidence: 83%